2006
DOI: 10.1542/peds.2006-2065
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Trichophyton tonsurans Through a Large Urban Child Care Center: Defining Infection Prevalence and Transmission Patterns by Molecular Strain Typing

Abstract: In contrast to dermatophyte infections in older individuals, where symptomatic disease seems to be a consequence of pathogen acquisition and carriers can be traced to an index case, in this preschool-aged population infection was endemic, and symptomatic disease seemed to represent activation of a single strain that persisted on the scalp.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
48
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 22 publications
0
48
0
1
Order By: Relevance
“…In more detail, NTS II was most frequently isolated from wrestlers in the Kansai area, but only a few Kansai strains were used in the study, and the only wrestling related strain from the Kansai area was found to be NTS II, suggesting that the frequency of (21). The stability of molecular markers may also be an issue, but serial passage over 36 months showed that the molecular types, including the VIR, remained stable (20).…”
Section: Molecular Typing Using Nts Regionsmentioning
confidence: 98%
“…In more detail, NTS II was most frequently isolated from wrestlers in the Kansai area, but only a few Kansai strains were used in the study, and the only wrestling related strain from the Kansai area was found to be NTS II, suggesting that the frequency of (21). The stability of molecular markers may also be an issue, but serial passage over 36 months showed that the molecular types, including the VIR, remained stable (20).…”
Section: Molecular Typing Using Nts Regionsmentioning
confidence: 98%
“…6 In addition, a study conducted with children in daycares in the United States revealed that between 22 to 50% of them exhibited symptoms of dermatophyte infection of the hair scalp. 7 In Brazil, the Southern and Southeast regions have a high incidence of infections caused by the dermatophyte Trichophyton rubrum, followed by Microsporum canis and Trichophyton mentagrophytes, whereas in the Northeast, Trichophyton tonsurans, T. rubrum and M. canis predominate. 8,9 In the State of Sao Paulo, 4,500 children (0-15 years old) were evaluated to determine the incidence of tinea capitis from 1996 to 2000.…”
Section: Epidemiological Aspectsmentioning
confidence: 99%
“…In the United States, where T. tonsurans is endemic among African American children, infection rates as high as 50% have been observed in large-scale epidemiologic investigations (2). Infection rates for species that are endemic in other geographic regions can be equally impressive.…”
Section: Discussionmentioning
confidence: 99%
“…However, careful optimization of the PCR amplification procedures ensured a singular, discernible pattern for each strain in the validation set (9). Yet subsequent application of our PCR-restriction fragment length polymorphism (PCR-RFLP)-based strain-typing methods to a large-scale epidemiologic investigation revealed composite RFLP patterns at this locus (2). Notably, examining coding region variations in conjunction with variations in the rDNA locus offered evidence that these patterns were consistent with infections comprised of more than one strain.…”
mentioning
confidence: 99%